El control interno de inventarios y su incidencia en los resultados económicos de la distribuidora dicolaic ubicada, en el Cantón Latacunga Provincia De Cotopaxi, periodo 2017 - Gagñay Vega, Jessica Alexandra (2017)
The current research project, its purpose is to evaluate the internal control of inventories and its impact on the economic results of the distributor DICOLAIC, through the application of internal control questionnaire in the warehouse areas and administration, being this way it allows to know a confidence level and a risk level; also the application of an analysis and indicators on financial statements of the distributor, which has helped to verify, the incidence of good inventory management, about the utility generated by the distributor, getting conclusions, which were issued in a precise manner, attaching to these the corresponding recommendations in order to improve in all aspects. The main purpose of the distributor DICOLAIC is to achieve financial success, as well as expanding the line of products to be distributed to achieve important business growth. This depends on many factors, among which is mentioned the importance of each entity processes, and that is framed in control, thus allow to give reasonable security. It is also important to mention that an adequate application of internal inventory control guides the direction of a distributor, strengthening and periodically adding value to its operations. Within the research project, it is considered important to include a special examination of the inventories component, applied to the distributor DICOLAIC, the same one that allows to evaluate the purchase and storage process. In addition, a financial analysis was carried out on 2017 period. For audit development, real and truthful documentary information was collected, as well as the internal control questionnaire and direct observation, through which data were obtained for present investigation elaboration, the same that allowed to confirm the applied procedures within the distributor.